Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = 78 x 31 + 78 x 24 + 78 x 17 + 22 x 72
A = 78 x ( 31 + 24 + 17 ) + 22 x 72
A = 78 x 72 + 22 x 72
A = 72 x ( 78 + 22 )
A = 72 x 100
A = 7200
C = 53 x 39 + 47 x 39 - 53 x 21 - 47 x 21
C = 39 x ( 53 + 47 ) - 21 x ( 53 - 47 )
C = 39 x 100 - 21 x 6
C = 3900 - 126
C = 3774
a) \(21^{15}=21^{3.5}=\left(21^3\right)^5=9261^5\)
Vì \(9261>27\Rightarrow9261^5>27^5\Rightarrow21^{15}>27^5\)
b) \(15^{12}=\left(3.5\right)^{12}=3^{12}.5^{12}\)
\(81^3.125^5=\left(3^4\right)^3.\left(5^3\right)^5=3^{4.3}.5^{3.5}=3^{12}.5^{15}\)
Vì \(3^{12}=3^{12}\)mà \(5^{12}< 5^{15}\Rightarrow3^{12}.5^{12}< 3^{12}.5^{15}\Rightarrow15^{12}< 81^3.125^5\)
a, ( - 168 ) + 72 . ( - 168 ) + ( - 168 ) . 27
= ( - 168 ) + ( - 12096 ) + ( - 4536 )
= - 12264 + - 4536
= - 16800
b, 22 . ( - 3 ) - ( 110 + 8 ) : ( - 3 )2
= 4 . ( - 3 ) - ( 1 + 8 ) : 9
= ( - 12 ) - 9 : 9
= ( - 12 ) - 1
= - 13
c, ( - 1075 ) - ( 29 - 1075 )
= ( - 1075 ) - ( - 1046 )
= - 29
d, ( - 9 ) + ( - 11 ) + 21 + ( - 1 )
= - 20 + 21 + ( - 1 )
= 1 + - 1
= 0
e, 30 + 12 + ( - 20 ) + ( - 12 ) - ( 30 - 20 ) + ( 12 - 12 )
= 42 + ( - 20 ) + ( - 12 ) - 10 + 0
= 22 + ( - 12 ) - 10 + 0
= 10 - 10 + 0
= 0 + 0
= 0
g, ( 13 - 135 + 49 ) - ( 13 + 49 )
= [( - 122 ) + 49 ] - 62
= ( - 73 ) - 62
= - 135
h, 35 - { 12 - [ ( - 14 ) + ( - 2 ) } ]
= 35 - { 12 - ( - 16 ) }
= 35 - 28
= 7
Bài 2:
a. x - 35 = ( - 12 ) - 3
x - 35 = - 15
x = - 15 + 35
x = 20
b, \(\frac{1}{4}\)+ \(\frac{1}{3}\): 3x = - 5
\(\frac{3}{12}+\frac{4}{12}\): 3x = - 5
\(\frac{7}{12}\): 3x = - 5
3x = \(\frac{7}{12}\): - 5
3x = \(\frac{-7}{60}\)
x = \(\frac{-7}{60}\): 3
x = \(\frac{-7}{180}\)
c,2x-1 = 8
2x-1 = 24
x = 4 + 1
x = 5
\(\text{|x| = - 20+27}\)
\(|x|=7\)
\(\Rightarrow\orbr{\begin{cases}x=7\\x=-7\end{cases}}\)
\(\text{12 - x=-21}\)
\(x=12+21\)
\(\Rightarrow x=33\)
\(\text{(x - 5).(-2)=72}\)
\(x-5=72:\left(-2\right)\)
\(x-5=-36\)
\(x=-36+5\)
\(\Rightarrow x=-31\)
học tốt
| x | = -20 + 27
|x| = 7
=> x = 7 hoặc x= -7
Vậy...
12-x = -21
x= 12- (-21)
x= 33
Vậy...
(x-5) (-2) = 72
x-5 = 72: (-2)
x-5 = -36
x= -36+5
x= - 31
Vậy....